Pengaruh Pertumbuhan Perusahaan, Profitabilitas dan Ukuran Perusahaan terhadap Struktur Modal pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2020-2022 - Fatonah, Anis; Rohmi, Misfi Laili (Budgeting: Jurnal Akuntansi Syariah, 2024)
The manufacturing sector is one of the largest contributors to Gross Domestic Product (GDP) in Indonesia. This sector continues to develop over time, although it has slumped due to the impact of the Covid pandemic that has hit almost all parts of the world. The purpose of this study is to examine the effect of company growth, profitability and company size on the capital structure of manufacturing companies on the Indonesia Stock Exchange. The method used in this study is a quantitative method, with a descriptive analysis approach and the data collection technique is documentation sourced from the official website of the Indonesia Stock Exchange through IDX, namely in the form of secondary data on financial statements that have been published from 2020-2022, there are 24 companies that are used as sample companies, namely companies that publish complete financial reports. The data taken is annual financial report data. Based on the results of the study, the conclusions of this study are 1) Company growth does not have a significant effect on capital structure, because the significance value is 0.781> 0.05. 2) Profitability has a significant effect on capital structure, because the significance value is 0.008 <0.05. 3) Company size has a significant effect on capital structure, because the significance value is 0.006 <0.05. 4) The results simultaneously show that company growth, profitability, and company size have a significant effect on capital structure, because the calculated F value is 5.440 and the significance value is 0.03 <0.05. 5) The adjusted R2 value is 0.214. This shows that capital structure is influenced by company growth, profitability and company size by 21.4, the rest is influenced by factors outside this study.